The effects of macroeconomic variables towards housing price in Malaysia / Nur Farahin Abdul Rahman - Abdul Rahman, Nur Farahin (Faculty of Business Management, 2017)
Over the past few years, house price in Malaysia has experienced significant price expansion and this situation became a worrying that causes distress especially to the current lenders. This study were an attempt to determine the macroeconomic variables that affected to house price in Malaysia and explored the relationship between the variables with house price. Only three macroeconomic variables such as Gross Domestic Product (GDP), Inflation Rate (CPI) and Population (Pop) were taken into this study with House Price Index (HPI) as dependent variable. This study consists of 127 observations of quarterly data for each variable starting from 1985 first quarter until 2016 third quarter. All data of HPI, GDP, CPI and Pop were taken or got from DataStream and then there were tested by using EViews8. Those data were analyzedusing descriptive analysis, unit root test, correlation matrix and regression analysis. It were then being analyzed using test on assumption such like normality test, test on variance error term, test on serial correlation of error term (BG Test) and multicollinearity (VIF Test). The results showed only GDP and Pop were positive and significantly related to HPI while CPI was not significant with HPI and only two hypotheses were rejected while the other one was failed to reject. A conclusion were made by given some proofs and evidence from the previous research or journal. Besides that, a few recommendation and limitation were listed in this study for uses and references to the future researchers.